Exhalation delivery system with fluticasone improves quality of life and health status: pooled analysis of phase 3 trials NAVIGATE I and II. Issue 7 (22nd May 2020) - Soler, Zachary M.; Colman, Sam; Velez, Fulton F.; Schlosser, Rodney J.
Abstract : Background: Chronic rhinosinusitis with or without nasal polyps (CRSwNP/CRSsNP) seriously impairs health‐related quality of life (HRQoL). This analysis describes the impact of the exhalation delivery system with fluticasone (EDS‐FLU) on HRQoL, assessed by the 36‐item Short‐Form Health Survey version 2 (SF‐36v2), and on utilities, assessed via the Short‐Form 6‐Dimension (SF‐6D), in patients with CRSwNP. Methods: Post hoc analysis of pooled randomized clinical trial data (NAVIGATE I and II; N = 643) to examine change from baseline in SF‐36v2 and SF‐6D at end‐of‐double‐blind (EODB: 16 weeks) and end‐of‐open‐label (EOOL: 24 weeks; following 8 weeks of open‐label treatment) for EDS‐FLU vs placebo (EDS‐PBO). Baseline characteristics predictive of change in SF‐36 and SF‐6D scores were assessed. Results: Mean baseline SF‐36v2 scores were below population norms. At EODB, mean improvement was greater for all SF‐36v2 domain and component scores with EDS‐FLU (range: 2.9 [physical functioning] to 5.11 [bodily pain BP]) vs EDS‐PBO (range: 0.81 [mental health] to 2.87 [BP]) (each comparison p < 0.01); physical and mental component score improvements within the EDS‐FLU group exceeded the minimal clinically important difference (MCID). Clinically meaningful and statistically significant improvements in SF‐6D utility scores were seen in EDS‐FLU–treated patients compared to EDS‐PBO–treated patients (0.058 vs 0.023, respectively, p < 0.001). At EOOL, SF‐36v2 and SF‐6D mean scores were at or above population norms, with clinically meaningful and statistically significant improvements from baseline. Conclusion: In this pooled analysis of 2 large pivotal EDS‐FLU trials, health domain and health utilities improvements were significantly greater with EDS‐FLU than EDS‐PBO and were comparable to population norms.